PERAN LITERASI DIGITAL DALAM MEMBENTUK GENERASI CERDAS, BIJAK, DAN SEHAT BERMEDIA SOSIAL - Fajri, Chotamul; Hanif Nur Khalis; Andini Resti Aprisha; Dewi Mutya Haq (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The rapid advancement of information technology requires today’s generation to possess adequate digital literacy skills in order to use social media intelligently, responsibly, and in a healthy manner. Digital literacy not only refers to the ability to search for and understand information, but also includes skills in processing, creating, and behaving ethically in the digital environment. This study aims to examine how digital literacy contributes to shaping a generation that is critical, wise in using social media, and capable of maintaining mental health during digital activities. The research method employed a literature study based on various references related to digital literacy and social media user behavior. The results of the analysis indicate that digital literacy plays an important role in improving the ability to evaluate information, preventing the spread of misinformation, strengthening digital ethics, and reducing risks such as cyberbullying and social media addiction. Therefore, strengthening digital literacy is a strategic step in building a generation that is better prepared to face digital challenges in a positive and productive manner.